(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Type 2 diabetes mellitus (T2DM) and vitamin D deficiency are both disorders of high prevalence in the world. Evidence supports an association between low vitamin D levels and risk for T2DM, and its complications. There remains insufficient evidence to suggest whether treatment of low vitamin D can prevent or improve T2DM. Aim: this review will focus on the current understanding of the role of vitamin D in the pathogenesis of T2DM, and questioning if vitamin D supplementation can improve the pancreatic function, thus providing a better glycemic control or slow down its complications. Conclusion and recommendation: deficient vitamin D levels increases the risk of developing T2DM. This finding highlights the need for conducting large-scale health screening to identify those at risk of DM using vitamin D blood level assessment. However, more studies are required to ascertain the effect of vitamin D supplementation in T2DM patients.